2001
DOI: 10.1093/humrep/16.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and neonatal outcome in women with a history of recurrent miscarriage: a cohort study

Abstract: Obstetric and neonatal outcomes of women who had a history of recurrent miscarriage were compared with a control population from 1 January 1992 to 30 June 1998. Amongst a total of 162 pregnancies which progressed beyond 24 weeks gestation in women with a history of recurrent miscarriage, there were four perinatal deaths and 16 babies were admitted to the special care baby unit. The rates of preterm delivery (13%), small-for-gestational-age (13%), perinatal loss (2.5%) and Caesarean section (36%) were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
1
11

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 12 publications
10
67
1
11
Order By: Relevance
“…Hammoud et al (18) also noted a small increased risk (odds ratio of 1.13) of PTB and PPROM in women with a history of one miscarriage. Our findings are consistent with other studies showing adverse outcomes with increasing number of miscarriages (18)(19)(20). The association between SAB and subsequent PTB was also confirmed in a recent meta-analysis (10).…”
Section: Commentsupporting
confidence: 94%
“…Hammoud et al (18) also noted a small increased risk (odds ratio of 1.13) of PTB and PPROM in women with a history of one miscarriage. Our findings are consistent with other studies showing adverse outcomes with increasing number of miscarriages (18)(19)(20). The association between SAB and subsequent PTB was also confirmed in a recent meta-analysis (10).…”
Section: Commentsupporting
confidence: 94%
“…3 In our study, we found that the incidence of primary RPL was 75%, consistent with study by also reported higher rates of primary RPL. [4][5][6] We found only one study which reported secondary RPL to be more common. 7 Majority of 53% women showed identifiable causes.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, three or more successive losses affect 1%-2% of women of reproductive age, and two or more successive losses affect approximately 5% (12). Although several causes of recurrent pregnancy loss have been identified, 38% of cases remain unexplained (13,14). Thrombophilias have been suggested as a possible cause of recurrent miscarriage (RM) (15).…”
Section: Inherited Thrombophilia and Recurrent Pregnancy Lossmentioning
confidence: 99%